Impact of unemployment on cardiovascular mortality in united states: a nationwide county-level analysis 2010–2019. (3rd October 2022) - Sayed, A; Aldosoky, W; Khalid, N; Diab, M; Elsaiey, A; Dar, T; Abohashem, S
Abstract: Background: Unemployment has been linked with a myriad of adverse health outcomes; however, its population-level impact on cardiovascular mortality (CVM), particularly amongst various demographic subgroups, remains understudied. Purpose: To determine the impact of county unemployment levels on CVM rates, in overall and between different demographic subgroups. Methods: We utilized the CDC WONDER database tool to retrieve county-level CVM rates for U.S. counties between 2010 and 2019. The County Health Rankings project was used to retrieve data on unemployment levels in each county as well as other characteristics used in an adjusted multivariate model. Generalized linear mixed models using Poisson regression were used to estimate the impact of unemployment on county-level CVM using relative (incidence rate ratios; IRR) and absolute (additional yearly deaths; AYD) measures. Results: From 2010 to 2019, a total of 2904 U.S. counties (64.2% white; 50.81% female) with data available on CVM and unemployment levels were analyzed. In a multivariate model adjusted for demographic composition, CV risk, socioeconomic, environmental, and healthcare-access factors, unemployment was significantly associated with higher levels of CVM (IRR: 1.026; 95% CI: 1.018 to 1.033; 6.00 AYD). The relative impact of unemployment was strongest in elderly Blacks (IRR: 1.051; 95% CI: 1.029 to 1.074), middle-aged whites (IRR: 1.050; 95% CI: 1.032 to 1.067), and middle-aged females (IRR: 1.046; 95% CI: 1.018 to 1.075). The absolute impact of unemployment was highest in elderly Blacks (AYD: 94.70), elderly Whites (AYD: 35.30), and elderly females (AYD: 32.70). On a relative basis, the impact was more pronounced in the middle-aged (IRR: 1.030; 95% CI: 1.015 to 1.044) compared to the elderly (IRR: 1.022; 95% CI: 1.014 to 1.030), females (IRR: 1.026; 95% CI: 1.017 to 1.036) compared to males (IRR: 1.022; 95% CI: 1.014 to 1.031), and Blacks (IRR: 1.036; 95% CI: 1.016 to 1.057) compared to Whites (IRR: 1.030; 95% CI: 1.022 to 1.038). Conclusion(s): Unemployment is significantly associated with county-level CVM, and this impact is most pronounced in vulnerable demographic subgroups, namely females and Blacks. Efforts to reduce unemployment levels may significantly lower the burden of cardiovascular disease, particularly in groups most strongly affected by health disparities. Funding Acknowledgement: Type of funding sources: None.